Teaching fellowships for UK foundation doctors. (2nd January 2015) - Qureshi, Shaun
Abstract: Teaching Fellowships for junior doctors in their second post-graduate (FY2) year should be considered by medical students and junior doctors in UK. FY2 Teaching Fellowships are available in many foundation schools as part of the UK Academic Foundation Programme. Although programme structures differ between schools, they are designed to allow junior trainees to take time out from clinical practice to develop their teaching skills and gain insights into medication education careers. The advantages of an FY2 teaching fellowship include valuable experience of teaching and formal feedback not available to other trainees; the opportunity to further develop your portfolio; further development of the trainee's own knowledge and skills; the stimulation of working with students. Potential drawbacks to be considered are reduced direct clinical contact; reduced salary; difficulty carrying out education research in the allocated time frame; occasional difficulties establishing the teacher–student relationship while the trainee is at a relatively junior level. Experience of medical education as an FY2 trainee provides a helpful stepping stone whether or not the trainee further pursues education as a career, because the teaching skills are transferable to any specialty, and the unique experience enhances the trainee's confidence as a role model for junior colleagues.